2010
DOI: 10.1007/s11144-010-0156-4
|View full text |Cite
|
Sign up to set email alerts
|

Detailed product and kinetic analysis for the low-pressure selective oxidation of isobutane over phosphomolybdic acid

Abstract: The selective oxidation of isobutane over phosphomolybdic acid has been analyzed using a low-pressure steady-state technique. Observed products are methacrolein, 3-methyl-2-oxetanone (a lactone), acetic acid, carbon dioxide and water. These products form in two distinct fashions designated Categories 1 and 2. Category 1 is exclusively observed with methacrolein and is consistent with a Bulktype (II) process. The lactone and acetic acid are Category 2 products and these form by the Bulk-type (I) mechanism. A ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 74 publications
(107 reference statements)
3
12
0
Order By: Relevance
“…Products observed from the reaction of isobutane with phosphomolybdic acid using this technique were methacrolein, 3-methyl-2-oxetanone (lactone), acetic acid, carbon dioxide and water; these selective oxidation products for isobutane over phosphomolybdic acid have been previously reported by Kendell et al [44,51]. For the metal substituted phosphomolybdates, methacrolein, lactone, carbon dioxide and water were also detected.…”
Section: Products Observed With Tprssupporting
confidence: 66%
See 4 more Smart Citations
“…Products observed from the reaction of isobutane with phosphomolybdic acid using this technique were methacrolein, 3-methyl-2-oxetanone (lactone), acetic acid, carbon dioxide and water; these selective oxidation products for isobutane over phosphomolybdic acid have been previously reported by Kendell et al [44,51]. For the metal substituted phosphomolybdates, methacrolein, lactone, carbon dioxide and water were also detected.…”
Section: Products Observed With Tprssupporting
confidence: 66%
“…Category 1 methacrolein kinetic parameters are listed in Table 5, where T range refers to the temperature span used in the modeling procedure. Errors associated with the kinetic values are expressed as parenthetic terms in Table 5 The Arrhenius parameters for isobutane selective oxidation over phosphomolybdic acid have been reported previously [51]. This work showed that the activation energy for category 1 methacrolein formation varied from 56.9 ± 1.5 to 149 ± 4 kJ mol -1 .…”
Section: Category 1 Methacrolein Parameterssupporting
confidence: 54%
See 3 more Smart Citations